STRENGTHENING POSITIVE IMAGE OF MARINE TOURISM ATTRACTIVE: A STUDY OF TANJUNG BAYANG BEACH, INDONESIA - Aliza Sabrina Mokodongan (Politeknik Pariwisata Makassar, 2025)
This study aims to understand and identify the actual conditions regarding the experiences and perceptions of tourists related to Tanjung Bayang Beach as a marine tourism destination and to provide strategies for strengthening its positive image. This research employs a qualitative method conducted at Tanjung Bayang Beach, Makassar City, from August to October 2025. Data were collected through in-depth interviews with five tourists in September 2025. The results show that the majority of tourists learned about Tanjung Bayang Beach from family and close friends, highlighting the importance of social networks and word-of-mouth in promoting the destination. However, regarding the assessment of beach cleanliness, the majority consensus was that the condition is still inadequate, making it an aspect that requires serious attention from the management. The quality of facilities and services received varied assessments, ranging from average to good, while the overall tourist attraction met visitors' expectations. The hospitality of the management and local community received excellent evaluations, becoming a positive strength of the destination. Therefore, it can be said that Tanjung Bayang Beach has become a favorite tourist destination for some tourists, allowing it to be developed further to provide greater benefits for the management and local communities involved. Strategies to achieve this include strengthening routine and structured beach cleanliness management programs, involving local communities and visitors in education and shared responsibility, which can enhance the destination's image. Additionally, improving service quality and facilities by providing friendly and responsive services, engaging all stakeholders in sustainable tourism resource management, and organizing cultural and sports events that involve local communities to attract more tourists and increase destination exposure. The results of this study indicate that strengthening the positive image of Tanjung Bayang Beach is highly dependent on the synergy between improving service quality, sustainable environmental management, and the active role of local communities as key players in tourism development. A pentahelix approach involving government, businesses, communities, academia, and media is essential to achieve sustainable and competitive destination development.